PERAN KEPALA SEKOLAH DALAM MENGIMPLEMENTASIKAN NILAI-NILAI PENDIDIKAN AGAMA ISLAM PADA PESERTA DIDIK DI SMA GUPPI SALAWATI KABUPATEN SORONG - S, Sukman (PRODI PENDIDIKAN AGAMA ISLAM (PAI) SEKOLAH TINGGI AGAMA ISLAM NEGERI MAJENE, 2024)
This study aims to describe the role of the principal in implementing the values that contain Islamic education and to identify the supporting and inhibiting fastors experienced by the principal in implementing the values that contain Islamic education. This research is a qualitative research. This type of research is field research. Methods of data collection using observation techniques, interviews and documentation. Furthermore, the data is presented in an appropriate from so that it is read and understood, then the data is analyzed and conclusions are drawn. The results of this study state tha: 1) the role of the principal in implementing values that contain Islamic religious education to GUPPI SAlawati high school students is maxzimized, it can be seen from the role of the principal which is very important for the progress of the school and fostering students about religion, namely a) implement Dhuha prayer, b) implement reading surah yasin, c) implement Zduhur player, d) implement lectures/cultum, e) implement recitation once a month. 2) supporting and inhibiting factors for the principal, including: a) supporting factors:i) there is support from 100% of teachers, ii) the environment around the school, b) inhibiting factors: i) parental factors, ii) heandpone factors, ii) community environmental factors.